2016
DOI: 10.1002/gps.4522
|View full text |Cite
|
Sign up to set email alerts
|

Both muscle mass and muscle strength are inversely associated with depressive symptoms in an elderly Chinese population

Abstract: Both muscle mass and muscle strength are inversely associated with depressive symptoms in elderly Chinese. These findings may provide novel insights linking skeletal muscle and depressive symptoms. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 28 publications
(47 reference statements)
4
25
0
Order By: Relevance
“…So far, an inverse association between cardiorespiratory fitness and risk of depression have been well-established among young ( 14 ) and middle-aged adults ( 15 ; 16 ) . Similarly, previous studies also reported an association between muscular strength and depression risk among the elderly population (17)(18)(19) . However, to our knowledge, there have been no reports yet on whether muscle strength has a significant association with depression at younger ages.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…So far, an inverse association between cardiorespiratory fitness and risk of depression have been well-established among young ( 14 ) and middle-aged adults ( 15 ; 16 ) . Similarly, previous studies also reported an association between muscular strength and depression risk among the elderly population (17)(18)(19) . However, to our knowledge, there have been no reports yet on whether muscle strength has a significant association with depression at younger ages.…”
Section: Introductionsupporting
confidence: 67%
“…For subject's characteristics, continuous variables were compared using analysis of variance (ANOVA), and categorical variables were compared by using chi-square tests. Currently, the relationship between higher handgrip strength (indicator of overall muscle strength), and lower risk of depressive symptoms is already widely accepted (17)(18)(19) . However, this relationship had not been previously confirmed among younger adults.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Reduction in grip strength was also reported to be associated with a higher risk of depressive symptoms. 9 , 20 In a recent cross-sectional survey, Wu et al 10 identified that both muscle mass and muscle strength were inversely associated with depressive symptoms in elderly Chinese individuals. Additionally, sarcopenic obesity was demonstrated to be positively associated with depressive symptoms 21 and lower indicators of psychological health, including perceived stress and suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“… 8 A prospective cohort study reported that lower handgrip strength (HS) was associated with depressive symptoms in Japanese individuals. 9 Additionally, Wu et al 10 recently identified that depressive symptoms are inversely associated with both muscle mass and muscle strength in elderly Chinese individuals. However, some findings have been inconsistent between studies; the data from the 2010–2011 Korean National Health and Nutrition Examination Survey reported that depression was not associated with sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…The reported factors of depression in old age include genetic susceptibility, chronic diseases, disability, pain, frustration with limitations in activities of daily living, personality trait, adverse life events (widowhood, separation, divorce, bereavement, poverty, social isolation) and lack of adequate social support (Levav & Rutz, 2002). Even lower muscle mass, lower muscle strength and vitamin D de ciency contribute to late-life depression (Wu et al, 2017;Okereke & Singh, 2016). These studies on risk factors of elderly depression have mainly been reported in the western countries, but seldom in Chinese population.…”
Section: Introductionmentioning
confidence: 99%